Campur Kode Bahasa Indonesia Dan Bahasa Kutai Dialeg Tenggarong Kota Di Kantor Desa Separi Kabupaten Kutai Kartanegara - Anwar, Muhammad; Arifin, Syaiful; Hefni, Asnan (Adjektiva: Educational Languages and Literature Studies, 2018)
This research was conducted to develop the Kutai language in the Tenggarong Kota dialect and at the same time as a contribution of knowledge related to the mixing of the codes for the Kutai language in the Tenggarong Dialect. Thus, local languages ​​can continue to be preserved so that speakers of regional languages ​​can use regional languages ​​according to their place and situation. The research objective was to determine the code mixing event that occurred in the Separi Village Office, Kutai Kartanegara Regency and to describe the insertion of language elements that was more dominant in the code mixing event. The method used in this qualitative research is observation, the observation method with basic techniques, namely tapping techniques and note taking techniques. The results showed that code mixing occurred in the Separi Village Office, Kutai Kartanegara Regency, between Indonesian and Kutai languages. The code mixing that occurs is indicated by the insertion of linguistic elements in the form of words, phrases and clauses. The most dominant insertion of linguistic elements in the code mixing process at the Separi Village Office, Kutai Kartanegara Regency, is the insertion of linguistic elements in the form of phrases.